2018
DOI: 10.1016/j.jjcc.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Late onset of atrial fibrillation in patients undergoing mitral valve repair for type II dysfunction

Abstract: Remodeling of the atrium caused by functional mitral stenosis is important for late Af, as well as recurrent MI. To prevent these problems, avoiding selection of a small ring at primary mitral repair for type II dysfunction and durable repair are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…3336 Magruder et al and similar studies found increasing postoperative LAD to be an independent predictor of late-onset AF when following patients submitted to mitral valve repair, even when excluding atrial fibrillation developed in the first 6 weeks. 37,38 This supports the idea postoperative structural remodeling provides an arrhythmic substrate facilitating AF development, which in turn contributes to the remodeling process.…”
Section: Discussionsupporting
confidence: 59%
“…3336 Magruder et al and similar studies found increasing postoperative LAD to be an independent predictor of late-onset AF when following patients submitted to mitral valve repair, even when excluding atrial fibrillation developed in the first 6 weeks. 37,38 This supports the idea postoperative structural remodeling provides an arrhythmic substrate facilitating AF development, which in turn contributes to the remodeling process.…”
Section: Discussionsupporting
confidence: 59%
“…Application of long-acting cardioplegia, such as del Nido cardioplegia, could be a solution to this problem. 26 The present overall 30-day mortality and 3-year survival rates were both 0%, with no significant differences between the 2 groups. Similar results were reported in other studies.…”
Section: Discussionmentioning
confidence: 42%
“…Several studies reported that smaller prostheses may result in a higher mean TMPG, and may inhibit reverse remodeling of the left atrium, which caused a risk of late atrial fibrillation. 8,19,20 Stress echocardiogram showed that a slight elevation of TMPG can be a risk for postoperative impaired exercise capacity and quality of life. 6,8,21 To improve operative quality of mitral repair for DMR, elevation of TMPG must be avoided; however, the cut-off value of mean TMPG ranged from 3.0 to 5.0 mmHg, and the definition of FMS, which can be a cause of cardiac adverse events, is still undetermined.…”
Section: Discussionmentioning
confidence: 99%